Impact of educational interventions on nurses' knowledge regarding care of patient with central venous line - Shrestha, R (Journal of Kathmandu Medical College, 2014)
Background: Central Venous Line is widely used in critically ill patients for continuous assessment of the cardiovascularsystem. Adequate knowledge of nurses in taking care of central venous pressure line plays vital role to minimizecomplications and to accurately recognize catheter-related problems, thus securing safer and improved outcome forthe patient. This study was performed to fi nd out the effectiveness of educational intervention in increasing nurses’ knowledge regarding care of patients with Central Venous Line among nurses. Methods: This is a pre-experimental study design (pre-intervention---intervention---post-intervention). After institutionalapproval, 40 nurses were taken from Kathmandu Medical College Teaching Hospital for study adopted with SimpleRandom Sampling (Lottery) method. A structured, self-administered questionnaire was used for pre- intervention datacollection After two weeks of educational intervention, post- intervention test was taken. The data was analysed andcalculated by using descriptive Statistics and Paired “t” test was applied to assess the differences between pre-interventionand post- intervention results. Results: Overall, mean knowledge score was 14.75 with SD 2.37 in the pre intervention. After educational interventionthe score was changed to 16.80 with SD 5.51. There was signifi cant difference between the pre -intervention and postinterventionknowledge score (p value =0.039).While assessing the overall existing knowledge level of the participants, most of the participants had moderate knowledgelevel (50% to 75%). After intervention knowledge level signifi cantly increased (p value=0.001). Conclusion: The study showed that educational intervention programme considerably improved the nurses’ level ofknowledge about care of patient with central line. Overall mean knowledge score between pre-intervention and postinterventionwas found to be significant. DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10553 Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013, page: 28-30